The optimum nutrition bible - Holford, Patrick (Piatkus, 1997)
Aimed at helping the reader to design a personal supplement programme that gives optimum nutrition. There is also a "Nutrient Fact File" that lists every nutrient known and and A-Z of nutritional healing, covering common ailments like allergies, fatigue, headaches and ulcers.